Market reaction of target firms value in M&AS emprical evidence from Turkey - İlhan, Öznur (İstanbul Bilgi Üniversitesi, 2017)
[Abstract Not Available]
Şirket birleşme ve devralmalarda hedef firma değerinin piyasa reaksiyonu